О сущности и моделях Конституции - Амандыкова, С.К. (Изд-во КарГУ., 2009)
Мақалада Конституцияның түсінігі мен мəні қарастырылады. Автор шетел жəне отандық ғалымдардың көзқарастарын зерттеу негізінде Конституцияның мəніне өзіндік интерпретация береді. Сонымен қатар қазіргі кездегі Конституцияның негізінде жатқан конституциялық теорияларға талдау жасайды. In the article of candidate of legal science, professor Amandykova S.K. the concept and nature of the constitution is given. On the basis of researching as of foreign, also of domestic scientists’ points of views, the author gives own interpretation of the nature of constitutionalism. Moreover the analysis of constitutional theories that lie in the basis of modern constitutions is given.